Best technologies for public libraries : policies, programs, and services - DeCristofaro, Christopher; Hutter, James; Tanzi, Nicholas (Libraries Unlimited, 2020)
"This book examines four technologies; 3D printing, drones, virtual reality, and augmented reality, and their place in the public library"--